Lesotho : Fourth Review Under the Poverty Reduction and Growth Facility Arrangement and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2003)
This paper assesses Lesotho's Fourth Review Under the Poverty Reduction and Growth Facility Arrangement and Request for Waiver of Performance Criteria. Lesotho's economic program was broadly on track through December 2002, but large fiscal slippages emerged by end-March 2003. IMF staff welcomes the government's strong commitment to its economic program and recommends completion of the fourth review. It supports a waiver for the nonobserved quantitative performance criterion because of the actions taken by the government to reduce nonessential spending in 2002/03 and because of its commitment to implement sustainable fiscal policies in the medium term.